Bean and beverage quality - Prospects of four F1 hybrids of coffee (Coffea arabica L.) in India - Das, Divya K.; Shivanna, M.B.; Prakash, N.S. (Journal of Plantation Crops, 2021)
In coffee, both physical quality attributes as assessed by the colour and size of the beans and cup quality of the beverage rated based on sensory analysis are the important criteria for determining market price. In general, quality is dependent on genotype and also influenced by the growing conditions. The bean and beverage quality of pure C. arabica varieties is far superior to diploid introgressed arabica genotypes developed for improved host resistance. Thus, integrating the host resistance without affecting quality parameters is very imperative in arabica coffee breeding. Four F1 hybrids (S.5083, S.5084, S.5085 & S.5086) developed from reciprocal crosses between the most popular semi-dwarf arabica variety ‘Chandragiri’ and Sln.10, an auto-tetraploid of a diploid inter-specific hybrid, used as a donor for rust resistance, were evaluated for physical quality traits for four seasons and cup profiles for two seasons. Among the four hybrids, S.5085 and S.5086 recorded bold bean size with 70.05 per cent and 69.75 per cent of mean ‘A’ grade beans, respectively. The ‘B’ grade ranged from 9.5 per cent to 10.4 per cent in hybrids as against 16.8 per cent in Chandragiri. The Pea berry ranged from 10.1 per cent to 12.5 per cent, indicating high fertility in hybrids. The cup qualities of S.5085 and S.5086 were also found superior with a cumulative average score of 80.3 and 78.3 respectively, compared to parents; 71.6 in Chandragiri and 77.3 in Sln.10. The present study established the superiority of S.5085 and S.5086 in quality parameters and therefore has potential implications in the commercial exploitation of these two F1 hybrids that also manifested high levels of field tolerance to coffee leaf rust.